Long QT Syndrome: Genetics and Future Perspective - Eimear Wallace; Linda Howard; Min Liu; Timothy O’Brien; Deirdre Ward; Sanbing Shen; Terence Prendiville (2019)
Long QT syndrome (LQTS) is an inherited primary arrhythmia syndrome that may present with malignant arrhythmia and, rarely, risk of sudden death. The clinical symptoms include palpitations, syncope, and anoxic seizures secondary to ventricular arrhythmia, classically torsade de pointes. This predisposition to malignant arrhythmia is from a cardiac ion channelopathy that results in delayed repolarization of the cardiomyocyte action potential. The QT interval on the surface electrocardiogram is a summation of the individual cellular ventricular action potential durations, and hence is a surrogate marker of the abnormal cellular membrane repolarization. Severely affected phenotypes administered current standard of care therapies may not be fully protected from the occurrence of cardiac arrhythmias. There are 17 different subtypes of LQTS associated with monogenic mutations of 15 autosomal dominant genes. It is now possible to model the various LQTS phenotypes through the generation of patient-specific induced pluripotent stem cell-derived cardiomyocytes. RNA interference can silence or suppress the expression of mutant genes. Thus, RNA interference can be a potential therapeutic intervention that may be employed in LQTS to knock out mutant mRNAs which code for the defective proteins. CRISPR/Cas9 is a genome editing technology that offers great potential in elucidating gene function and a potential therapeutic strategy for monogenic disease. Further studies are required to determine whether CRISPR/Cas9 can be employed as an efficacious and safe rescue of the LQTS phenotype. Current progress has raised opportunities to generate in vitro human cardiomyocyte models for drug screening and to explore gene therapy through genome editing.